2009
DOI: 10.2355/isijinternational.49.1063
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Non-metallic Inclusions in the Nucleation of Acicular Ferrite in Steels

Abstract: The effects of non-metallic inclusions in nucleating acicular ferrite in steels during cooling from a weld or cooling from an austenitic temperature are reviewed. The influence of the acicular ferrite (AF) structure on mechanical properties of steels such as strength and toughness is briefly mentioned. The different factors affecting the formation of acicular ferrite, such as the soluble content of alloying elements in steel, cooling rate from austenitizing temperature, austenite grain size and inclusion chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
221
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(247 citation statements)
references
References 65 publications
4
221
0
6
Order By: Relevance
“…[10,49,50] Pure MnS particles are often described as inert and only MnS layers on other inclusion types are observed to promote acicular ferrite formation. In contrast, the results of the current study have shown that pure MnS particles were also active.…”
Section: Interaction Of Solute Manganese and Manganese Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,49,50] Pure MnS particles are often described as inert and only MnS layers on other inclusion types are observed to promote acicular ferrite formation. In contrast, the results of the current study have shown that pure MnS particles were also active.…”
Section: Interaction Of Solute Manganese and Manganese Inclusionsmentioning
confidence: 99%
“…This effect was first observed for weld metals. [8] Comprehensive reviews on the formation of acicular ferrite have been done by Bhadeshia [9] as well as Sarma et al [10] Up to now, C-Mn-(Ni) weld metals [11][12][13][14][15] were the most investigated material related to the formation of acicular ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados por Ricks et al [7]. Conforme Sarma et al [4] esta faixa de tamanho de inclusões seria o normal encontrado em aços carbono, com algumas, mas nem todas, atuando como formadores de ferrita acicular.…”
Section: Resultsunclassified
“…A formação da estrutura de ferrita acicular pode ser provocada pela adição controlada de elementos químicos microligantes nos aços, por exemplo: Ti, Al, Nb, V, O, N, Ce, B e S [4]. De acordo com [5], o potencial de nucleação intragranular varia com o tipo de inclusões e as mais efetivas são as que contem Ti, Ca e S. Outra característica importante seria o tamanho das inclusões, quanto maiores se tornariam sítios preferenciais da nucleação da ferrita acicular, resultando na transição entre ser ou não ser nucleante em função do seu tamanho [6].…”
Section: Introductionunclassified
See 1 more Smart Citation